Acordos internacionais de investimento, propriedade intelectual e saúde Global: políticas de controle do tabaco e o ODS 3.a. - Borges, Luciana Correia (2018)
This study focuses on the clashing relationship between the adoption of international agreements to protect foreign investment and States’ obligation to respond to public health needs. Primarily, it aims at demonstrating to which extent three key-elements part of the International Investment Agreements (IIAs) impact States’ legislative autonomy to implement Tobacco Control policies. The research contribution is twofold. Firstly, it seeks to investigate the possible consequences resulting from provisions that affect Intellectual Property (IP) protection, as well as from investor-state arbitration, on States’ policy space for achieving compliance with the Framework Convention on Tobacco Control (FCTC). Concomitantly, illustrating the research results, it aims at indicating Alternative Model BITs as the most appropriate ones to internalise the Plain Packaging Act, a measure which is emphasised by FCTC guidelines and reinforced by Sustainable Development Goal (SDG) 3.a. To that end, the specialised literature was reviewed through a systematic research strategy aimed at compiling and appraising key-areas related to the quest for balancing foreign investment protection with public health policies internalisation. To achieve the proposed objectives, an analysis comparing the US 2004-2012 Model BIT, the URU-SUI BIT, the AUS-HK BIT , TPP and KORUS investment chapters (which synthesize the Standard Model) with the Alternative Model BITs (Alternative Brazilian and Indian Model BITs) was also conducted. Finally, a specific analysis of two cases was conducted: Australia v. Philip Morris e Uruguay v. Philip Morris. The results attested that IIAs that follow the Standard Model apparatus cause what has been addressed as "regulatory chill", mitigating States’ policy space for implementing cost-effective public health policies. It was also understood that SDG 17 Targets strengthen the argument behind the necessity of disseminating the Alternative Brazilian Model BIT and promoting the internalisation of the Plain Packaging Act, as they propose a new approach to development, aligned with the Model's apparatus.